Agora: An open platform for exploration of Alzheimer's disease evidence: Genetics/omics and systems biology. (7th December 2020) - Greenwood, Anna K.; Gockley, Jake; Daily, Kenneth; Aluthgamage, Duminda; Leanza, Zoë; Sieberts, Solveig K.; Woo, Kara H.; Simon, Stockard; Gendel, Alina; Thyer, Tess; Do, Khai; Doerr, Megan; et al.
Abstract: Background: New therapies for treating Alzheimer's Disease (AD) are urgently needed. Discovery‐based research approaches have identified a host of promising new AD targets across a spectrum of therapeutic hypotheses. However, progress to validate selected targets and develop new experimental reagents and therapeutics requires efforts beyond the focus of any single research group. We have built the Agora site as an open repository that publicly shares information about new AD targets to facilitate target evaluation by the broader AD research community. Method: Agora aggregates information and experimental resources in support of nascent AD targets. We are expanding Agora to catalog evidence and experimental reagents being generated by the Open Drug Discovery Center for AD (Open‐AD). Result: Agora is available at https://agora.ampadportal.org . Agora presents a list of nominated targets stemming from the Accelerating Medicines Partnership in AD (AMP‐AD) consortium and the broader AD research community. Agora also hosts interactive visualizations designed to support non‐bioinformaticians in the evaluation of data from RNAseq, proteomic, and metabolomic studies. Updates to Agora in support of the new Open‐AD center include 1) presentation of individual scorecards for nominated targets based on multiple lines of evidence and 2) a new exploration framework in which targets are mapped onto therapeutic hypotheses. Conclusion: Agora is a platform to enable the AD research community to unite around promising target hypotheses.